Caffeine: friend or foe in the modern combat environment? - Stein, Jesse A. (Kansas State University, 2020)
This dissertation identified critical tasks (CTs) executed in modern combat environments and determined caffeine’s effect on CT performance. Job task analyses have identified CTs performed by specific military occupations, but have yet to identify CTs from combat environments. A job task analysis was conducted in Study 1 to identify CTs performed in modern combat environments. Subject matter experts meeting international criteria developed a job analysis questionnaire (JAQ). The JAQ contained 19 combat-relevant tasks that were evaluated for task frequency and importance by 137 veterans from the Global War on Terror. Eighty-nine percent of combat-relevant tasks were CTs that spanned multiple domains of physical fitness and tactical proficiencies. The most important CTs were: “sprint all-out in a single or repeated-bout < 30-s,” “sprint, jump, or dive under combat load,” and “aim, fire, and prepare a weapon in support of operations.” Optimizing soldier performance during CTs is key to mission-success and soldier survivability. Soldiers utilize caffeine as a countermeasure during sustained operations; yet, caffeine’s utility during these CTs remain unknown. In Study 2, we determined the effects of acute caffeine supplementation on exercise tolerance during repeated-sprint exercise. Ten physically active men were randomized in a double-blind crossover study to consume caffeine (5 mg/kg) or placebo before an intermittent critical velocity test. Subjects performed 3 sets of repeated-sprints (10 s running, 10 s rest) until exhaustion at 110%, 120%, and 130% of peak velocity (PV) achieved during a graded exercise test. Caffeine supplementation prolonged exercise duration at 110% PV (294-s vs. 392-s, p = 0.020), but not at 120% and 130% PV. Study 2 found that caffeine was ergogenic at approximately 400-s – similar in duration to tactical combat engagements – and gave precedence for the final investigation. Study 3 combined CTs “sprint, jump, or dive under combat load” and “aim, fire, and prepare a weapon in support of operations” to develop a tactical combat movement simulation and determine caffeine’s effects on CT performance. Thirty-nine healthy subjects were randomized in a double-blind, crossover study to chew caffeine gum (4 mg/kg) or placebo before a tactical combat movement simulation that included a fire-and-move battle drill and a marksmanship with cognitive workload assessment. Subjects wore a weight vest (~25-kg) during the simulation to mimic a combat load. Sprint durations from the fire-and-move simulation were used to model susceptibility to enemy fire. Sprint duration and susceptibility to enemy fire increased by 9.3% and 7.8%, respectively during the tactical combat movement simulation (p = 0.001). Cognitive performance also decreased during the tactical combat movement simulation (p < 0.05). Caffeine had no effect on sprint duration, susceptibility to enemy fire, marksmanship or cognitive performance. Overall, caffeine may provide benefit for some CTs when performed in isolation at select running velocities, but not when CTs are performed concurrently.
Keywords: Ergogenic; Exercise tolerance; Criticality; Survivability